2013
DOI: 10.1111/jcmm.12080
|View full text |Cite
|
Sign up to set email alerts
|

Impaired surface expression and conductance of the KCNQ4 channel lead to sensorineural hearing loss

Abstract: KCNQ4, a voltage-gated potassium channel, plays an important role in maintaining cochlear ion homoeostasis and regulating hair cell membrane potential, both essential for normal auditory function. Mutations in the KCNQ4 gene lead to DFNA2, a subtype of autosomal dominant non-syndromic deafness that is characterized by progressive sensorineural hearing loss across all frequencies. Despite recent advances in the identification of pathogenic KCNQ4 mutations, the molecular aetiology of DFNA2 remains unknown. We re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 63 publications
0
39
0
Order By: Relevance
“…Consequently, the Wnt/β-catenin signaling pathway activity was impaired, leading to compromised cochlear morphogenesis (Figure 11 ). In addition, mutations in KCNQ4 (Gao et al, 2013 ; Wang et al, 2014 ) and STRC (Francey et al, 2012 ) can induce sensorineural deafness, but this has not been found with PAX6.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the Wnt/β-catenin signaling pathway activity was impaired, leading to compromised cochlear morphogenesis (Figure 11 ). In addition, mutations in KCNQ4 (Gao et al, 2013 ; Wang et al, 2014 ) and STRC (Francey et al, 2012 ) can induce sensorineural deafness, but this has not been found with PAX6.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in KCNQ genes cause inherited diseases, as follows: (a) Mutations of KCNQ1 cause heart diseases, including long QT syndrome; (b) those of KCNQ2 or KCNQ3 cause benign neonatal seizures; and (c) mutations of KCNQ4 result in ADNSHL (DFNA2) (Brown, ; Maljevic et al., ). DFNA2 is characterized by progressive sensorineural hearing loss at all frequencies (Gao, Yechikov, Vazquez, Chen, & Nie, ; Kubisch et al., ). As the molecular basis of these diseases is reduction of Kv7 potassium channel activity, resulting from mutations, small compounds that activate these channels, so‐called “channel openers,” have been developed as a strategy for treatment of these conditions (Wulff, Castle, & Pardo, ).…”
Section: Introductionmentioning
confidence: 99%
“…Missense mutations at the K + ion selectivity filter with the GYG signature sequence (p.Gly285Cys, p.Gly285Ser) or pore-helix domain (p.Leu274His, p.Trp276Ser) showed complete loss of ion conduction and decreased surface expression. Thus, these mutants exhibit strong dominant-negative effects to WT protein, and their impaired conductance was not rescued by co-assembly with conducting WT subunits 4 , 5 , 18 , 21 , 31 . In the YUHL35 family, the novel KCNQ4 missense mutation at the K + channel pore forming region (p.Asp266Tyr) produced non-conducting homotetrameric KCNQ4 channels and decreased the sensitivity to KCNQ channel openers, but did not affect membrane trafficking or the formation of heteromultimeric channels with WT subunits.…”
Section: Discussionmentioning
confidence: 99%
“…KCNQ4 (MIM 600101, Kv7.4) is a voltage-gated potassium channel that plays essential roles in maintaining ion homeostasis and regulating hair cell membrane potential 4 . KCNQ4 mutations cause deafness nonsyndromic autosomal dominant 2 (DFNA2), which is characterized by progressive sensorineural hearing loss at all frequencies 4 , 5 . Kcnq4 −/− mice exhibit degeneration of outer hair cells and progressive hearing loss 6 .…”
Section: Introductionmentioning
confidence: 99%